Green Synthesis and Characterization of Iron Oxide Nanoparticles Using Egeria densa Plant Extract - Maruf Olaide Yekeen; Mubarak Ibrahim; James Wachira; Saroj Pramanik (Applied Biosciences, 2025)
An aqueous leaf extract of Egeria densa was used to green-synthesize iron (II) and iron (III) oxide nanoparticles from ferrous sulphate and ferric chloride, respectively. The successful green synthesis of the nanoparticles was confirmed through UV–visible spectroscopy, and the colour of the mixtures changed from light-yellow to green-black and reddish-brown for FeO–NPs and Fe2O3–NPs, respectively. The morphological characteristics of the nanoparticles were determined using an X-ray diffractometer (XRD), a Fourier transform infrared spectrophotometer (FTIR), a transmission electron microscope (TEM), and energy-dispersive X-ray spectroscopy (EDX). The UV–Vis spectrum of the FeO–NPs showed a sharp peak at 290 nm due to the surface plasmon resonance, while that of the Fe2O3–NPs showed a sharp peak at 300 nm. TEM analysis revealed that the FeO–NPs were oval to hexagonal in shape and were clustered together with an average size of 18.49 nm, while the Fe2O3-NPs were also oval to hexagonal in shape, but some were irregularly shaped, and they clustered together with an average size of 27.96 nm. EDX analysis showed the presence of elemental iron and oxygen in both types of nanoparticles, indicating that these nanoparticles were essentially present in oxide form. The XRD patterns of both the FeO–NPs and Fe2O3–NPs depicted that the nanoparticles produced were crystalline in nature and exhibited the rhombohedral crystal structure of hematite. The FT-IR spectra revealed that phenolic compounds were present on the surface of the nanoparticles and were responsible for reducing the iron salts into FeO–NPs and Fe2O3–NPs. Conclusively, this work demonstrated for the first time the ability of Elodea aqueous extract to synthesize iron-based nanoparticles from both iron (II) and iron (III) salts, highlighting its versatility as a green reducing and stabilizing agent. The dual-path synthesis approach provides new insights into the influence of the precursor oxidation state on nanoparticle formation, thereby expanding our understanding of plant-mediated nanoparticle production and offering a sustainable route for the fabrication of diverse iron oxide nanostructures. Furthermore, it provides a simple, cost-effective, and environmentally friendly method for the synthesis of the FeO–NPs and Fe2O3–NPs using Egeria densa.